2020
DOI: 10.1021/acs.analchem.9b05531
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Aptamer Modified Graphene Field-Effect Transistor Nanosensor for Label-Free and Specific Detection of Hepatocellular Carcinoma-Derived Microvesicles

Abstract: Cancerous microvesicles (MVs), which are heterogeneous membrane-bound nanovesicles shed from the surfaces of cancer cells into the extracellular environment, have been widely recognized as promising “biofingerprints” for various cancers. High-performance identification of cancerous MVs plays a vital role in the early diagnosis of cancer, yet it is still technically challenging. Herein, we report a gold nanoparticle (AuNP)-decorated, dual-aptamer modified reduced graphene oxide (RGO) field-effect transistor (AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 51 publications
1
53
0
1
Order By: Relevance
“…Graphene biosensors exhibit the advantages of miniaturization, a low limit of detection, high sensitivity, and simplicity of design. Several research groups have reported the use of graphene sensors for the measurement and detection of chemical and biological components and target biomarkers for diseases, including cancer markers, DNA, and glucose [ 16 , 17 ]. However, the above-mentioned applications directly immobilize and functionalize receptor molecules on the graphene surface.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene biosensors exhibit the advantages of miniaturization, a low limit of detection, high sensitivity, and simplicity of design. Several research groups have reported the use of graphene sensors for the measurement and detection of chemical and biological components and target biomarkers for diseases, including cancer markers, DNA, and glucose [ 16 , 17 ]. However, the above-mentioned applications directly immobilize and functionalize receptor molecules on the graphene surface.…”
Section: Introductionmentioning
confidence: 99%
“…Additional strategies in the design of the interface have also been reported to enhance signal strength, such as the addition of protective layers 162 or addition of gold nanoparticles. 120,198 Importantly, the detailed structure of the interface is often weakly characterized: in particular, the density of probe molecules on graphene is usually poorly controlled and often unknown, in large part because it is difficult to measure experimentally. In consequence, there is little quantitative knowledge on the correlation between interface design and the resulting LOD (or any other performance metrics).…”
Section: Limit Of Detection and Sensitivitymentioning
confidence: 99%
“…In such assays, target molecules are most commonly diluted in blank saline buffer, 42,88,90,117 sometimes with a calibrated mix of interfering species. 53,55,83,91,118 These calibration assays are usually presented as a proof of concept for the sensors, and they are sometimes used as positive controls before assays on cell culture samples, 51,56 clinical samples 55,115,121,136,198 or other environmental samples, 46,123 in which the concentration is either unknown or measured with another detection technique to compare results. For instance, Wang et al 121 were the first group to measure the concentration of lead ions in real blood samples with GFET sensors, using a calibration with positive controls in buffer.…”
Section: Replicas and Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this challenge, aptamers have been applied as the receptors of FET biosensors, utilizing their ability to recognize small molecules and conformational changeability. [5][6][7] Aptamers, which are only several nanometers in size, can be artificially designed and selected from a large oligonucleotide library via the systematic evolution of ligands by exponential enrichment (SELEX). 8,9 In particular, the ease of the structural design of aptamers allows for the introduction of conformational changeability with the binding of the target molecule.…”
Section: Introductionmentioning
confidence: 99%